(untitled) (Research, Society and Development, 2021)
This study aims to understand the contributions of health professionals to the sexual and reproductive education of adolescents. It is an integrative literature review, with a qualitative approach, carried out by searching for articles indexed in the Virtual Health Library (VHL), with the help of the following databases: Scientific Electronic Library Online (SCIELO), National Center for Biotechnology Information (PUBMED), Latin American and Caribbean Literature in Health Sciences (LILACS). The inclusion criteria include literature review surveys available in the databases described, between the years 2000 to 2020. As exclusion criteria, articles were not considered for monetary reward, incomplete and not converging with this study. After applying the inclusion and exclusion criteria, 14 scientific articles remained. The results show the adolescents’ inadequate information and knowledge regarding issues of sexuality and prevention of early pregnancy, considering the need for a broader sexual education with spaces for dialogues and discussions of doubts by the adolescents, both at school and in the context familiar. Therefore, it is of great importance that health professionals participate and cooperate in the education process of adolescents, promoting access to information regarding contraceptive methods, knowledge about STDs and guidelines regarding the consequences of an early pregnancy for their lives. family, school or professional life, reflecting on personal projects.